Research on dam-break flow induced front wave impacting a vertical wall based on the CLSVOF and level set methods. (15th April 2019) - Li, Y.L.; Yu, C.H.
Abstract: The problem of a dam-break flow induced front wave impacting a vertical wall placed at the downstream end was numerically investigated by using the Level Set (LS) method and Coupled Level Set/Volume Of Fluid (CLSVOF) method. For the LS approach, the advection equation of the level set function to capture the interface is discretized by the fifth-order, weighted, essentially non-oscillatory (WENO5) scheme. For the CLSVOF approach, the Tangent of Hyperbola for Interface Capturing/Weighed Line Interface Calculation (THINC/WLIC) scheme is adopted to capture the interface and improve mass conservation. The interface normal vector in the WLIC reconstruction procedure can be estimated from the LS function instead of VOF function. The Navier–Stokes solver which uses an explicit Adams–Bashforth algorithm is performed on a staggered Eulerian grid. The numerical experiments are carried out in a rectangular flume with a smooth horizontal wet bed with four different tailwater levels. This study investigates the formation and propagation of the negative wave resulting from the reflection of flood waves against the downstream end wall. The numerical results are compared with laboratory experiment results studied in Ref (Kocaman and Ozmen-Cagatay, 2015 ). and a reasonable agreement is achieved. Numerical results show that the CLSVOF solutions are better than LS solutions in terms of mass conservation.